Nanocompósitos de AgNPs funcionalizadas com os constituintes do LCC e galactomanana com potencial atividade antileishmania - Bezerra, Thayllan Teixeira (2019)
Leishmaniasis is one of the Neglected Tropical Diseases, transmitted by female sandflies contaminated with protozoa of the genus Leishmania. The treatment of the disease consists of the administration of pentavalent antimonials, drugs of high toxicity to the protozoan and to the human body. In view of the need for new studies to produce less toxic and more efficient drugs, this work aimed at the development of a new nanocomposite with potential application in this area, with silver nanoparticles (AgNPs) synthesized within micellar aggregates formed by the constituents of the Cashew Nut Shell Liquid (CNSL): Anacardic Acid, Cardanol, Cardol, and the respective sodium salts derived therefrom. The critical micellar concentration of these compounds was calculated in the presence and absence of AgNPs, determining the best synthetic conditions. The use of microwave irradiation increased the reaction yield compared to the conventional method. The conductivity, UV-Vis, Fluorescence, Zeta Potential, and DLS analyzes showed that the salts of the CNSL constituents better stabilized the AgNPs and promoted higher yields. The AgNPs were immobilized in galactomannan of Adenanthera pavonina L. seeds and analyzed by Diffuse Reflectance Spectroscopy to observe the RPSL bands, confirming the presence of nanoparticles in the solid. No changes were observed in the optical properties of AgNPs, indicating that the immobilization process did not alter the shape and size of the NPs. In addition to preventing aggregation and agglomeration of NPs, galactomannan increases the biocompatibility of nanomaterials, since macrophages have a mannose receptor, allowing oral or topical delivery, without damaging the cell. This allows the constituents of LCC and AgNPS to be delivered into the cell and can attack the protozoan by attacking glycolytic enzymes and blocking the oxidative response mechanisms, respectively.